1997
DOI: 10.1073/pnas.94.26.14483
|View full text |Cite
|
Sign up to set email alerts
|

Localization of a constitutively active, phagocyte-like NADPH oxidase in rabbit aortic adventitia: Enhancement by angiotensin II

Abstract: Superoxide anion (O 2 ؊ ) plays a key role in the endogenous suppression of endothelium-derived nitric oxide (NO) bioactivity and has been implicated in the development of hypertension. In previous studies, we found that O 2 ؊ is produced predominantly in the adventitia of isolated rabbit aorta and acts as a barrier to NO. In the present studies, we characterize the enzyme responsible for O 2 ؊ production in the adventitia and show that this enzyme is a constitutively active NADPH oxidase with similar composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
332
4
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(359 citation statements)
references
References 50 publications
13
332
4
7
Order By: Relevance
“…Nox1 in vascular smooth muscle participates in cell proliferation [46], while Nox4 in these cells participates in maintenance of the differentiated phenotype [47,48]. Nox2 and associated regulatory proteins are also expressed in adventitia, where they contribute to constitutive ROS generation [49] and to Angiotensin II-induced vascular tone in part through inactivation of NO by superoxide [50]. In addition, Nox5 is expressed in vascular smooth muscle [51] and [Petumnetcha and Lambeth, unpublished].…”
Section: Nox Enzymes In the Cardiovascular System A Nox Enzymes In Cmentioning
confidence: 99%
“…Nox1 in vascular smooth muscle participates in cell proliferation [46], while Nox4 in these cells participates in maintenance of the differentiated phenotype [47,48]. Nox2 and associated regulatory proteins are also expressed in adventitia, where they contribute to constitutive ROS generation [49] and to Angiotensin II-induced vascular tone in part through inactivation of NO by superoxide [50]. In addition, Nox5 is expressed in vascular smooth muscle [51] and [Petumnetcha and Lambeth, unpublished].…”
Section: Nox Enzymes In the Cardiovascular System A Nox Enzymes In Cmentioning
confidence: 99%
“…In the vasculature, the endothelial as well as adventitial NAD(P)H oxidase is composed of gp91 phox (Nox2) and p22 phox , as well as p47 phox and p67 phox and the G protein Rac1 (88,245). It is now established that NAD(P)H oxidase expressed in endothelial cells is an important source of free oxygen radical generation in the arterial wall (147).…”
Section: Nistala Et Al 2060mentioning
confidence: 99%
“…10,11 Recent in vivo and in vitro studies have implicated the adventitial fibroblast as a major site for superoxide production in response to angiotensin II administration, 12,13 and we have recently shown that adventitial fibroblasts are a major source of the inducible form of NO synthase in aortic tissue after the in vivo administration of endotoxin to produce an inflammatory response. 14 To begin to evaluate the possible role of NO in modulating vascular remodeling during hypertension, we have used procedures for obtaining adult rat adventitial fibroblasts in culture and have studied the effects of NO on cell proliferation under standardized conditions in which quiescent cells were stimulated with FCS.…”
mentioning
confidence: 99%